Modern Methods of Repair of Paralytic Lagophthalmos (Ukrainian Journal of Ophthalmology, 2026)
Modern Methods of Repair of Paralytic Lagophthalmos
Keywords: paralytic lagophthalmos; facial nerve palsy; gold implant; lower lid ectropion correction; tarsorrhaphy